2020
DOI: 10.3390/ma13183930
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of UV Laser-Induced Porous Graphene Patterns with Nanospheres and Their Optical and Electrical Characteristics

Abstract: Many studies have been conducted to fabricate unique structures on flexible substrates and to apply such structures to a variety of fields. However, it is difficult to produce unique structures such as multilayer, nanospheres and porous patterns on a flexible substrate. We present a facile method of nanospheres based on laser-induced porous graphene (LIPG), by using laser-induced plasma (LIP). We fabricated these patterns from commercial polyimide (PI) film, with a 355 nm pulsed laser. For a simple one-step pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
2
1
Order By: Relevance
“…At this distance to focus, during the laser scan, the incidence spot of the beam emitted a bright white light indicative of the formation of a localized plasma. This is similar to what can be seen in the formation of LIG on polyimide, for both CO 2 and UV lasers, [ 43,44 ] indicating that the used parameters (including distance to focus) are close to those appropriate for LIG synthesis. However, the lack of immediate transformation at the start of the laser scan, only initiating from random spots further into the irradiated area, is still observed (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 82%
“…At this distance to focus, during the laser scan, the incidence spot of the beam emitted a bright white light indicative of the formation of a localized plasma. This is similar to what can be seen in the formation of LIG on polyimide, for both CO 2 and UV lasers, [ 43,44 ] indicating that the used parameters (including distance to focus) are close to those appropriate for LIG synthesis. However, the lack of immediate transformation at the start of the laser scan, only initiating from random spots further into the irradiated area, is still observed (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 82%
“…NPLIG could deliver a specific areal capacitance of 239 F g −1 at the current density of 0.05 A g −1 . This specific areal capacitance was superior to that for the LIG without hybrid atoms doping reported in previous studies at the same current density, 50 and it was also superior to the values obtained in previous research on GO-derived supercapacitors. 51–54 The high specific capacitance value of the NPLIG supercapacitor encountered here may be attributed to the hierarchical porous structure, which resulted in the high capacitance.…”
Section: Resultscontrasting
confidence: 47%
“…The excellent characteristic of the flexibility of the patterns is that they maintain the electrical characteristics after a bending test. The LIG patterns fabricated from laser scanning speeds of 20 mm/s and 40 mm/s showed a flat slope, which indicates good flexibility [59]. The thermal performance studies obtained for the LIG heaters with an area of 100 mm 2 are shown in Figure 5d.…”
Section: Electrical and Thermal Properties Of Lig Patternmentioning
confidence: 89%